PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORDWALL TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR EKONOMI SISWA KELAS XI SMA N 2 PERCUT SEI TUAN - Nur Sakinah; Muhammad Yusuf (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by interactive Wordwall media on learning motivation and economic learning outcomes of grade XI students at SMA Negeri 2 Percut Sei Tuan simultaneously and partially. The background of this study is driven by low student learning motivation and a high percentage of economic learning achievements that remain below the Learning Progress Minimum Criteria (KKTP). The research method applied was quantitative with a quasi-experimental approach using the Non-Equivalent Pretest-Posttest Control Group Design. The population comprised all grade XI students at SMA Negeri 2 Percut Sei Tuan, totaling 4 class. The sampling technique used was purposive sampling, which designated class XI-H (36 students) as the experimental class treated with the TGT model assisted by Wordwall media, and class XI-I (36 students) as the control class utilizing the direct learning model. Data on learning motivation were collected via a questionnaire with a Likert scale, while data on learning outcomes were gathered through objective multiple-choice tests. The research instruments were tested for validity and reliability prior to implementation. Data analysis techniques involved descriptive statistics and inferential analysis using Multivariate Analysis of Variance (MANOVA). The results indicated that: (1) There is a positive and significant effect of the TGT learning model assisted by Wordwall media on students' learning motivation and economic learning outcomes simultaneously, proven by the Wilks' Lambda significance value of 0.000 (Sig. < 0.05). (2) There is a positive and significant effect of the TGT learning model assisted by Wordwall media on students' learning motivation partially, indicated by a significance value of 0.000 (Sig. < 0.05). (3) There is a positive and significant effect of the TGT learning model assisted by Wordwall media on students' economic learning outcomes partially, indicated by a significance value of 0.001 (Sig. < 0.05). The features of team competition and digital gamification through Wordwall are proven effective in reducing the tediousness of conceptual material and boosting students' active participation. Keywords: Teams Games Tournament (TGT); Wordwall; Learning Motivation; Economic Learning Outcomes.   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif tipe Teams Games Tournament (TGT) berbantuan media interaktif Wordwall terhadap motivasi belajar dan hasil belajar ekonomi siswa kelas XI SMA Negeri 2 Percut Sei Tuan. Latar belakang penelitian ini didasarkan pada rendahnya motivasi belajar siswa serta banyaknya capaian hasil belajar ekonomi yang masih berada di bawah Kriteria Ketercapaian Tujuan Pembelajaran (KKTP). Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan eksperimen semu (Quasi-Experiment) menggunakan desain Non-Equivalent Pretest-Posttest Control Group Design. Populasi dalam penelitian ini mencakup seluruh siswa kelas XI SMA Negeri 2 Percut Sei Tuan yang mengikuti pelajaran ekonomi sebanyak 4 kelas. Teknik pengambilan sampel menggunakan purposive sampling, yang menetapkan kelas XI-H (36 siswa) sebagai kelas eksperimen dengan perlakuan model TGT berbantuan media Wordwall dan kelas XI-I (36 siswa) sebagai kelas kontrol dengan model pembelajaran langsung. Pengumpulan data motivasi belajar menggunakan instrumen angket dengan skala Likert, sedangkan data hasil belajar dikumpulkan melalui tes obyektif pilihan ganda. Instrumen penelitian telah diuji validitas dan reliabilitasnya sebelum digunakan. Teknik analisis data menggunakan statistik deskriptif dan analisis inferensial Multivariate Analysis of Variance (MANOVA). Hasil penelitian menunjukkan bahwa: (1) Terdapat pengaruh positif dan signifikan model pembelajaran TGT berbantuan media Wordwall terhadap motivasi belajar dan hasil belajar ekonomi siswa secara simultan, dibuktikan dengan nilai signifikansi uji Wilks' Lambda sebesar 0,000 (Sig. < 0,05). (2) Terdapat pengaruh positif dan signifikan model pembelajaran TGT berbantuan media Wordwall terhadap motivasi belajar siswa secara parsial, ditunjukkan oleh nilai signifikansi 0,000 (Sig. < 0,05). (3) Terdapat pengaruh positif dan signifikan model pembelajaran TGT berbantuan media Wordwall terhadap hasil belajar ekonomi siswa secara parsial, ditunjukkan oleh nilai signifikansi 0,001 (Sig. < 0,05). Karakteristik pembelajaran berbasis kompetisi tim dan gamifikasi digital melalui Wordwall terbukti efektif dalam memotong kejenuhan materi konseptual serta meningkatkan keterlibatan aktif siswa. Kata kunci: Teams Games Tournament (TGT); Wordwall; Motivasi Belajar; Hasil Belajar Ekonomi.